Investigation of the asymptotics of a renewal matrix - Buhrii, N.V. (Інститут математики НАН України, 2006)
A semi-Markov process with ﬁnite state space and continuous time without ﬁniteness condition of a mean stay time of this process in every ﬁxed state is considered. The asymptotic behaviour of the renewal matrix at inﬁnity is established under condition that the distribution tail of the stay time of the semi-Markov process in every ﬁxed state is a regularly varying function at inﬁnity with exponent −1.